MMP9High Neutrophils are Critical Mediators of Neutrophil Extracellular Traps Formation and Myocardial Ischemia/Reperfusion Injury - Shiyu Hu; Feng Zhang; Jingpu Wang; Jian Zhang; Chenguang Li; Yang Lyu; Yiwen Wang; Rong Huang; Yang Gao; Hongbo Yang; Juying Qian; Wenwen Tang; et al. (Advanced Science)
Abstract Neutrophil extracellular traps (NETs) are increasingly recognized as pivotal players and potential therapeutic targets in neutrophil‐mediated reperfusion injury. Despite their importance, the effects and variability of circulating neutrophils in relation to NET formation during myocardial ischemia/reperfusion injury (MI/RI) remain inadequately characterized. In this study, single‐cell transcriptomes of neutrophils isolated from the blood of healthy donors and MI/RI patients are analyzed. The results reveal that MI/RI neutrophils transition from a high IFIT1 expression profile into four distinct states, two of which exhibit elevated MMP9 transcription. These MMP9High neutrophil subpopulations are instrumental in the NET formation and correlate positively with the severity of MI/RI. Further investigation identifies the transcription factor SPI1 as a key regulator of this transition, acting through modulation of CST7 expression. Targeting SPI1 or CST7 significantly reduces the prevalence of MMP9High neutrophils and NET formation, resulting in improved MI/RI outcomes. These findings offer new insights into neutrophil heterogeneity and pinpoint a specific subset critical for NET formation, underscoring their potential as diagnostic biomarkers and therapeutic targets for MI/RI management.